2023
DOI: 10.1111/jar.13119
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative methodological approaches involving participants with intellectual disabilities: Scoping review of literature exploring death and dying

Abstract: BackgroundA paucity of qualitative research on sensitive topics that focuses on participants with intellectual disabilities leaves their views unexplored. This scoping review mainly aimed to provide an overview of qualitative data collection methods used in research involving participants with intellectual disabilities to explore death and dying.MethodA scoping review of primary research and methodological papers published between January 2008 and March 2022 was conducted. The PRISMA‐ScR checklist was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Guidance should mirror the consensus statement from Frankena et al (2019) on conducting inclusive health research with people with intellectual disabilities, providing guidelines specifically for researchers. In order to consider the range of impairments and preferences that people with intellectual disabilities possess, any structured guidance must (perhaps paradoxically) consider the need for flexibility in methods (Diaz, Bickenbach, Sabariego, & Bernard, 2023). Guidelines that respond to the needs of people with intellectual disabilities must also consider those with severe or profound intellectual disabilities, so they do not unintentionally leave out those who are typically not engaged as participants in research (Kirkendall et al, 2017).…”
Section: Providing Structured Methodological Guidance On Undertaking ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Guidance should mirror the consensus statement from Frankena et al (2019) on conducting inclusive health research with people with intellectual disabilities, providing guidelines specifically for researchers. In order to consider the range of impairments and preferences that people with intellectual disabilities possess, any structured guidance must (perhaps paradoxically) consider the need for flexibility in methods (Diaz, Bickenbach, Sabariego, & Bernard, 2023). Guidelines that respond to the needs of people with intellectual disabilities must also consider those with severe or profound intellectual disabilities, so they do not unintentionally leave out those who are typically not engaged as participants in research (Kirkendall et al, 2017).…”
Section: Providing Structured Methodological Guidance On Undertaking ...mentioning
confidence: 99%
“…However, there is no similar guidance on sensitive topics related to death and dying. A recently published scoping review (Diaz, Bickenbach, Sabariego, & Bernard, 2023) provided an overview of qualitative data collection methods used in research involving participants with intellectual disabilities to explore death and dying. Investigating 25 articles representing 23 research studies, this review identified that structured methodological guidance is required in order to adequately design and conduct research studies on a sensitive topic that may experience more scrutiny during the ethics approval process.…”
Section: Current Methodological Guidancementioning
confidence: 99%
See 2 more Smart Citations